Enteric-coated mycophenolate sodium immunosuppression in renal transplant patients: efficacy and dosing - Cooper, Matthew A.; Zeier, Martin (Transplantation reviews, 2012)
Mycophenolate mofetil (MMF), a mycophenolic acid (MPA) formulation, has improved both short- and long-term outcomes following renal transplantation, but is often associated with gastrointestinal (GI) complications that can lead to dose reduction or discontinuation, potentially jeopardizing patient outcomes. Enteric-coated mycophenolate sodium (EC-MPS) delivers equivalent MPA exposure to MMF and offers the potential to reduce GI burden (while maintaining patient safety). Here we review the efficacy of EC-MPS compared with MMF in renal transplant patients in terms of biopsy-proven acute rejection and graft loss, and examine the use of EC-MPS in newer regimens such as intensified dosing and calcineurin inhibitor minimization.